Hydrogen production from glucose degradation in water and wastewater treated by Ru-LaFeO3/Fe2O3 magnetic particles photocatalysis and heterogeneous photo-Fenton. (25th January 2018) - Iervolino, G.; Vaiano, V.; Sannino, D.; Rizzo, L.; Galluzzi, A.; Polichetti, M.; Pepe, G.; Campiglia, P.
Abstract: An optimized Ru-doped LaFeO3 photocatalyst was coupled with magnetic Fe2 O3 particles and was tested in the photocatalytic hydrogen production from glucose degradation under visible light irradiation. The catalysts were successfully synthesized by solution combustion synthesis using citric acid as organic fuel. Complete glucose degradation and hydrogen production of 5460 μmol/L was obtained after 4 h of irradiation using composite containing 67 wt% of Ru-doped LaFeO3 . After seven cycles of reuse, the photocatalytic activity did not change, evidencing the high stability of the magnetic photocatalyst, which can be recovered from the photoreactor using an external magnetic force. The recyclable sample was finally tested in the treatment of real wastewater from cherries washing process, and a very high hydrogen production (12344 μmol/L) was achieved. Finally, the possibility to couple the photocatalytic process (used for the production of hydrogen) with a heterogeneous photo-Fenton process was investigated in order to mineralize the unconverted organics in the wastewater coming from the photoreactor. Graphical abstract: Highlights: Photocatalytic H2 production from glucose on magnetic Ru-doped LaFeO3 /Fe2 O3 . Ru-doped LaFeO3 /Fe2 O3 is stable after several reuse cycles. Coupling the photocatalytic reactor with photo-Fenton system. Good performances also for the treatment and valorization of a real wastewater.